1999
DOI: 10.1136/gut.45.4.495
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Helicobacter pylori eradication on the natural history of lymphocytic gastritis

Abstract: Background-Lymphocytic gastritis is characterised by an accumulation of lymphocytes in the surface epithelium of the stomach. Lymphocytic gastritis has been linked to coeliac disease and Helicobacter pylori infection. Aims-To determine whether H pylori eradication leads to resolution of the lymphocytic infiltrate and clinical improvement in patients with lymphocytic gastritis, and to determine their HLA status. Methods-The Leeds Dyspepsia Questionnaire (LDQ) was administered to 13 patients with lymphocytic gas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
3
3

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(77 citation statements)
references
References 16 publications
3
68
3
3
Order By: Relevance
“…Different reports regarding an association between H. pylori eradication and subsequent decreases in duodenal IEL counts have found conflicting results. 32,33 Our results suggest that H. pylori colonisation should not be considered a significant cause of duodenal lymphocytosis, and should not, by any means, preclude the further assessment for the possibility of CD in these patients.…”
Section: Discussionmentioning
confidence: 95%
“…Different reports regarding an association between H. pylori eradication and subsequent decreases in duodenal IEL counts have found conflicting results. 32,33 Our results suggest that H. pylori colonisation should not be considered a significant cause of duodenal lymphocytosis, and should not, by any means, preclude the further assessment for the possibility of CD in these patients.…”
Section: Discussionmentioning
confidence: 95%
“…Lymphocytic gastritis in patients with celiac disease is more likely to involve the antrum, whereas corpus-predominant lymphocytic gastritis is more likely to represent Helicobacter infection (87,95). Lymphocytic gastritis due to H. pylori infection may resolve after elimination of the infection (83,88,89).…”
Section: Lymphocytic Gastritismentioning
confidence: 99%
“…Some studies described a correlation between Hp infection and the increase of gastric and duodenal IEL without villous atrophy [20,25]. Moreover both studies showed that Hp eradication is associated with a decrease in both gastric and duodenal IEL count, suggesting that duodenal intraepithelial lymphocytosis outside CD may be the result of an immune response to luminal antigens, such as Hp, analogous to the response to gluten in celiac patients.…”
Section: Resultsmentioning
confidence: 99%
“…Several authors also a correlation with lymphocytic gastritis (LG) which is also the most frequent form of gastritis observed in celiac patients [8][9][10][11]20,21].…”
Section: Resultsmentioning
confidence: 99%